Flash-Based KWL Interactive Media for TIMSS Oriented Reading Comprehension Skills - CarlosAndrés Gómez Salazar; Reny Radkova Buneva; Tatiana Ciocoi; Zulgadda Abdulkarimli (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aims to develop and validate Flash-based interactive learning media integrated with the K-W-L strategy to enhance eleventh-grade students’ reading comprehension skills and align instructional practices with higher-order cognitive demands reflected in international assessments such as the Trends in International Mathematics and Science Study (TIMSS). Methodology: This research employed a Research and Development (R&D) design adapted from the Borg and Gall model. The study involved eleventh-grade students in a public senior high school. Data were collected through expert validation sheets, reading comprehension tests (pre-test and post-test), and student response questionnaires. Data analysis included descriptive percentage analysis and N-Gain calculation. Main Findings: The developed media achieved an average expert validation score of 88.18%, categorized as good and feasible for classroom implementation. The effectiveness test showed a mean N-Gain score of 0.51, indicating moderate improvement in students’ reading comprehension. Significant gains were observed in higher-order indicators, including inference-making, interpretation of implicit meaning, and evaluation of contextual information aligned with TIMSS cognitive demands. Novelty/Originality of this study: This study integrates the K-W-L metacognitive strategy systematically within Flash-based interactive media to support analytical reading skills aligned with international assessment competencies. Unlike prior studies focusing solely on strategy use or media feasibility, this research bridges digital instructional design, structured reading strategy, and global literacy challenges in secondary education.